Patterns of income distribution in the Northern States of Malaysia: A life cycle approach - Shakil, Nurul Syifaa Mohd; Mohd, Saidatulakmal; Bahari, Zakaria; Hamat, Abdul Fatah Che (2015)

(untitled)
Income distribution can be defined as equality in which income is dealt out among members of a society. Income distribution is measured by how much income is earned by different segments of a population. In Malaysia, a common measure of income distribution is through calculating mean monthly income. The reported mean monthly income uses macroeconomic data segregated into ethnicity, states and urban-rural. At present, there is no income distribution measurement specifically for the Northern States of Malaysia. Therefore this study aims to estimate and identify the patterns of income distribution using different categories of income. The categories of income used are employment income, property income and gross income. This study uses 2009 Household Income Survey (HIS) data where 30 per cent of total observations are used. The findings confirm the LCH theory. There are different peak ages with different categories of income. However, the peak is not as high as proposed by Modigliani and Brumberg (1954). Calculation of mean income of different categories shows that the income from employment takes a large portion of total income.